Pengaruh Persepsi Bidang Perpajakan, Motivasi Karir, Penghargaan Finansial, Pengetahuan Pajak dan Kepercayaan Diri terhadap Minat Berkarir di Bidang Perpajakan (Studi pada Mahasiswa Akuntansi di Kabupaten Kudus) - Lisasanti, Indrya Septi; Mulyani, Sri; Ashsifa, Izza (TECHNOBIZ : International Journal of Business, 2024)
This research aims to determine the effect of perception in the field of taxation, career motivation, financial rewards, tax knowledge, and self-confidence on a career in taxation. This research was conducted by taking a population of students majoring in accounting at the Kudus Regency. The sampling method used was the purposive sampling method with the characteristics of active students majoring in accounting who have completed taxation courses, with a total sample of 321 respondents. Data collection in this research was done by distributing questionnaires offline and online in the form of a series of statements filled in by respondents and measured using a Likert scale. The data analysis method used in this study is multiple linear regression analysis using SPSS version 26. The results of this study show that perception in the field of taxation, career motivation, and self-confidence have a positive effect on interest in a career in taxation, while financial reward and tax knowledge have no effect on interest in a career in taxation.